A PATRIARCHAL IDENTIFICATION OF THE MOVIE KETTIYOLAANU ENTE MALAKHA THROUGH MULVEY’S MALE GAZE THEORY - Divyalekshmi. B; Chellarian , B. Sonia (International Journal of Psychosocial Rehabilitation, 2020)
Marital rape, a social sensitive issue which been given little attention over the decades had been remained in the four walls as a silent crime, and this silence extends to the media too. The issue of marital rape is not directly portrayed in Malayalam films, instead such movies turn out to show domestic violence, which is a modified form. In that way Kettiyolaanu Ente Malakha can be considered as one of the primary movies which discuss marital rape as a social issue. Despite dealing with such an issue, filmmakers tried to manipulate the audience to believe all is fine when it is not. The paper thus broadly traces all the aspects involved in respect with the theory of male gaze. The paper also tries to examine and question the central character’s innocence as well as the representation of marital rape as common issue in the light of Male Gaze theory.